Determinants of Vertical Integration: Financial Development and Contracting Costs - ACEMOGLU, DARON; JOHNSON, SIMON; MITTON, TODD (Journal of Finance, 2009)
ABSTRACT We study the determinants of vertical integration in a new data set of over 750,000 firms from 93 countries. We present a number of theoretical predictions on the interactions between financial development, contracting costs, and the extent of vertical integration. Consistent with these predictions, contracting costs and financial development by themselves appear to have no effect on vertical integration. However, we find greater vertical integration in countries that have both greater contracting costs and greater financial development. We also show that countries with greater contracting costs are more vertically integrated in more capital‐intensive industries.